The re-gendering of body and voice in Nura Amin's 'Let's Play Doctor'. Issue 6 (18th August 2022) - Hamdan, Mohammed
ABSTRACT: This article re-investigates the conventional understanding of the female body and voice in 'Let's Play Doctor', a short story written by the Egyptian Nura Amin in 2005. In traditional representations of women in literary discourses, female bodies have mostly been viewed as complex entities and unsettled fields for scientific practices that enhance and sustain the image of, in particular, male doctors as superior and authoritative. The male monopoly over scientific knowledge produces forms of social regulation within which female bodies are generally represented as passively and morally inferior. In the history of the medical profession, these bodies are registered as having the potential to enact aberrant, erotic, self-indulgence and fantasy, an act which makes them liable to shame and hence constant pathological examination. Amin's characters, however, offer a potent renunciation of the long established place/image of the female body in medical literary discourses through the irony of a simple children's game. By creating a community of young female actors who play a traditional game of doctor and patients, these young characters redirect our attention to the hidden power of female knowledge which is suppressed by social medical prejudices carried out on women in a highly gendered Arab society (Egypt).